Intrinsic two-way shape memory effect in a Ni-Mn-Sn metamagnetic shape memory microwire. (15th May 2020) - Chen, Zhen; Cong, Daoyong; Zhang, Yin; Sun, Xiaoming; Li, Runguang; Li, Shaohui; Yang, Zhi; Song, Chao; Cao, Yuxian; Ren, Yang; Wang, Yandong
Abstract: An intrinsic two-way shape memory effect with a fully recoverable strain of 1.0 % was achieved in an as-prepared Ni50 Mn37.5 Sn12.5 metamagnetic shape memory microwire fabricated by Taylor-Ulitovsky method. This two-way shape memory effect is mainly owing to the internal stress caused by the retained martensite in austenite matrix, as revealed by transmission electron microscopy observations and high-energy X-ray diffraction experiments. After superelastic training for 30 loading/unloading cycles at room temperature, the amount of retained martensite increased and the recoverable strain of two-way shape memory effect increased significantly to 2.2 %. Furthermore, a giant recoverable strain of 11.2 % was attained under a bias stress of 300 MPa in the trained microwire. These properties confer this microwire great potential for micro-actuation applications.